EFEK DINAMIKA LINGKUNGAN SEBAGAI MODERASI PENGARUH INOVASI TERHADAP KINERJA KEUANGAN (STUDI EMPIRIS SEKTOR TELEKOMUNIKASI DI BURSA EFEK INDONESIA) - Yuliani Yuliani (Research Center and Case Clearing House PPM School of Management, 2014)
This study aims to describe and analyze the direct effect of innovations on the financial performance, to measure and analyze the effects of environmental dynamics as a moderating influence innovation on the financial performance. The study was conducted in the telecommunications sector in Indonesia Stock Exchange (IDX) with the observation period 2008-2012. The sampling method is saturated. The unit of analysis of 30 cases by using Structural Equation Modeling (SEM)-based variance that is SmartPLS Ver 2.0 M3. Research findings that innovation is significant and positive effect on financial performance. Effects of environmental dynamics as a quasi moderating influence is weakening innovation on financial performance.